Latest trends in training martial arts athletes: a study of the contents of articles published in the journal «Teoriya i praktika fizicheskoy kultury» - Maltsev, G. S.; Zekrin, F. H.; Zebzeev, V. V.; Gulyaev, A. Y. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify current trends in the training of martial artists based on the content analysis of publications in the journal TiPFK.